Spondylodiscitis in Geriatric Patients: What Are the Issues?. Issue 1 (April 2023) - Herren, Christian; von der Hoeh, Nicolas Heinz; Zwingenberger, Stefan; Sauer, Daniel; Jung, Norma; Pieroh, Philipp; Drange, Steffen; Pumberger, Matthias; Scheyerer, Max J.; ,
Study Design: Review article. Objectives: A review of literature on the treatment of pyogenic spondylodiscitis in geriatric patients was performed with the aim to give an overview about these special patients and a recommendation on necessary diagnostics as well as conservative and operative treatment options. Methods: A systematic computerized literature search was done by the spondylodiscitis working group of the German Society for Orthopedics and Trauma Surgery. Results: Spondylodiscitis has an increasing incidence by age with a peak at 75 years or older. The 1-year mortality without an appropriate treatment is with 15 to 20% extremely high. Pathogen detection is the essential diagnostic step and the basis for a sufficient antibiotic treatment. Geriatric patients have initially less elevated inflammatory parameters. Compared to younger patients. They have a longer length of hospital stay and take longer for CRP normalization. Even the outcome between conservative and operative treatment is comparable after one year. Patients with spinal instability, immobilizing pain, epidural abscess, and newly emerged neurological deficits should be considered for operative treatment. Conclusions: The treatment of geriatric patients with pyogenic spondylodiscitis must take into account that these patients usually have multiple comorbidities. The main goals are resistance-based antibiotics and the shortest possible time of immobilization of the patient.